2011
DOI: 10.3390/s110605873
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Porous Composite Film for the Fabrication of a Hydrogen Peroxide Sensor

Abstract: A series of dopant-type polyaniline-polyacrylic acid composite (PAn-PAA) films with porous structures were prepared and developed for an enzyme-free hydrogen peroxide (H2O2) sensor. The composite films were highly electroactive in a neutral environment as compared to polyaniline (PAn). In addition, the carboxyl group of the PAA was found to react with H2O2 to form peroxy acid groups, and the peroxy acid could further oxidize the imine structure of PAn to form N-oxides. The N-oxides reverted to their original f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…In the N 1s scans, peaks assignable to N + –C, N–C, and N=C were observed at 400.9, 399.5, and 398.2 eV, respectively (Figure 2). 34,35 In the case of the mPBI powder, relative areas of N–C and N=C peaks largely increased, and that of the N + –C peak decreased compared with that of the other samples (Figure 2a, see also the Supporting Information, Table S1a), which indicated the loss of the cation group through the S N 2 reaction, as explained in Scheme S1. It is noted that only some of the mPBI powder dissolved and the XPS measurements were obtained from the residual powder.…”
Section: Resultsmentioning
confidence: 88%
“…In the N 1s scans, peaks assignable to N + –C, N–C, and N=C were observed at 400.9, 399.5, and 398.2 eV, respectively (Figure 2). 34,35 In the case of the mPBI powder, relative areas of N–C and N=C peaks largely increased, and that of the N + –C peak decreased compared with that of the other samples (Figure 2a, see also the Supporting Information, Table S1a), which indicated the loss of the cation group through the S N 2 reaction, as explained in Scheme S1. It is noted that only some of the mPBI powder dissolved and the XPS measurements were obtained from the residual powder.…”
Section: Resultsmentioning
confidence: 88%
“…For the ZnO/Au electrode, no obvious redox peak was observed at a scan rate (n) of 0.05 V s À1 in the range of 0.6 V to À0.6 V. However, the CVs obtained using the SPAnNa/Au electrode displayed one pair of significant redox peaks at 0.11 V and À0.14 V, which were attributed to the electrochemistry of the leucoemeraldine-leucoemeraldine radical cations. 35 When the ZnO nanoparticles were incorporated into the SPAnNa, the anodic and cathodic peaks were located at 0.09 V and À0.13 V, respectively, with a peak-peak separation of 0.22 V, which is smaller than that observed for the SPAnNa/Au electrode and indicates that the ZnO nanoparticles induced reversibility in the electrochemical reaction. 36 Furthermore, the redox current significantly increased, which indicates that the ZnO nanoparticles could amplify the electroactivity of SPAnNa because of the resulting enhancement of the surface area and conductivity.…”
Section: Characterization Of Spanna-zno Nanocompositesmentioning
confidence: 83%
“…Those indicated that the Cd nanoparticles that incorporated in PSNs can enlarge significantly the distance of inter particles PSNs or PSNs interface in line with the particles density of PSNs/CdMNp that lower compared to that of pristine PSNs. This fact has a very important implication for porous material fabrication which is widely used in technological processes associated with adsorption and catalysis phenomena [13,20]. Moreover, here, we propose a constant of 4.0 as constant of conversion to calculate nanoparticles density in either every square or circle area with 500 nm side lengths or 500 nm diameter lengths.…”
Section: Bulletin Of Chemical Reaction Engineering and Catalysis 7 (3)mentioning
confidence: 97%